2015
DOI: 10.3389/fpls.2015.00542
|View full text |Cite
|
Sign up to set email alerts
|

Coping with drought: stress and adaptive responses in potato and perspectives for improvement

Abstract: Potato (Solanum tuberosum L.) is often considered as a drought sensitive crop and its sustainable production is threatened due to frequent drought episodes. There has been much research aiming to understand the physiological, biochemical, and genetic basis of drought tolerance in potato as a basis for improving production under drought conditions. The complex phenotypic response of potato plants to drought is conditioned by the interactive effects of the plant's genotypic potential, developmental stage, and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
219
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(236 citation statements)
references
References 263 publications
9
219
0
8
Order By: Relevance
“…Plants under water stress have been reported to show a decrease in leaf conductance (Obidiegwu et al, 2015), total area of leaves (Albiski et al, 2012), reduced plant chlorophyll content (Anithakumari et al, 2012), and the photosynthesis rate (Li et al, 2015). Loggini et al (1999), and Apel and Hirt (2004) reported that drought inhibits or slows down photosynthetic carbon fixation mainly through limiting the entry of CO 2 into the leaf or directly inhibiting metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants under water stress have been reported to show a decrease in leaf conductance (Obidiegwu et al, 2015), total area of leaves (Albiski et al, 2012), reduced plant chlorophyll content (Anithakumari et al, 2012), and the photosynthesis rate (Li et al, 2015). Loggini et al (1999), and Apel and Hirt (2004) reported that drought inhibits or slows down photosynthetic carbon fixation mainly through limiting the entry of CO 2 into the leaf or directly inhibiting metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that has limited seed potato production in many parts of Kenya is unreliable rainfall. Potato is sensitive to soil water deficit (Bowen, 2003;Kiziloglu et al, 2006) and is often considered as a drought sensitive crop and its sustainable production is threatened due to frequent drought episodes (Obidiegwu et al, 2015). Plant needs for water and nutrients are interdependent, as a good water supply improves the nutritional status of crops, and adequate nutrient supply saves water (Roy et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These limitations can be measured with different variables such as the maximum photochemical efficiency of photosystem II (F v /F m ) (Xu et al, 2010). The photosynthetic rate in many cases is also affected by the chlorophyll (Chl) content (Obidiegwu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Potato plants are very sensitive to drought stress compared to other species (Porter et al, 1999). It has been reported that drought stress considerably decreases yield, making water availability a limiting factor in the production of this crop (Lahlou et al, 2003;Tourneux et al, 2003a;Obidiegwu et al, 2015). In South American countries, potato is cultivated in highly mountainous areas with few or no available water, suggesting that this crop is often subjected to drought stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…During the first two weeks of July, the LAI decreased, which can be explained by growth-reducing effects caused by a dry period with high temperatures in the area where the study site was located. The insufficient water availability due to the lack of rain, combined with the high temperatures can affect the stomatal capacity of leaves, which in turn can cause a reduction biomass, and thus LAI [52]. Flight 2 on 19 July 2016 occurred after the potato plants were flowered, and the haulm length increased to 0.6-0.9 m. Due to the drought and high temperatures, stems had fallen over and started filling up the space between the potato rows.…”
Section: Crop Developmentmentioning
confidence: 99%